SAT0551 Location Dependence of the Microstructure of Cartilage and of Subchondral Cortical and Trabecular Bone Microstructure in Knees with NO or Mild OA Assessed by High Resolution Micro-Computed Tomography. (10th June 2014) - Relier, M.; Touraine, S.; Bouhadoun, H.; Engelke, K.; Laredo, J.-D.; Chappard, C.
Abstract : Background: Loss of articular cartilage and alterations in subchondral bone architecture with the thickening of the cortical subchondral plate and trabeculae are important characteristics of osteoarthritis (OA). The local heterogeneity of these structures in knees with no or mild OA is unknown. Its quantification could help to better understand the changes induced in osteoarthritis. Objectives: To determine whether in non OA knees the relationship among cartilage volume, subchondral plate volume and porosity and structural parameters of the subchondral trabecular bone are location dependent. Methods: Twenty two left cadaveric knees, with no or mild medial femoro-tibial osteoarthritis (Kellgren-Lawrence grading scale <2) were selected based on radiographs from 13 women and 9 men (mean age 80.9±10.0 years). After dissection, 3 vertical cores (7mm in diameter, 10 mm in length) were extracted in the posterior (S1), inner (S2) and lateral (S3) region of the medial tibial plateau. S1 and S3 were located under the meniscus. The cores were imaged twice with micro-CT (Skyscan 1172®, voxel size 10.23 mm): first using the native extracted cores to characterize cartilage and again after defatting to characterize cortical and trabecular bone architecture. The following parameters were assessed: cartilage volume (CartVol, mm 3 ) and for the cortical subchondral bone: bone volume (BV_sub_chonPl, mm 3 ) and porosity (PoV/TV_sub_chonPl, %). In the subchondral trabecular bone, the following structural parameters were measured in the first 7 mm beneath the subchondral plate: Bone Volume/Total Volume (BV/TV, %), trabecular number (Tb.N, 1/mm), trabecular thickness (Tb.Th, mm), trabecular separation (Tb.Sp, mm), and degree of anisotropy (DA). One-way analysis of variance (ANOVA, Kruskal-Wallis), followed by post-hoc analysis for multiple range test (Tukey-Kramer), and Pearson correlation coefficients r (Spearman in case of non normality, r) were used to investigate group differences in cartilage and bone structure. Results: The table shows mean ± SD values for the analyzed parameters and ANOVA results. In addition for all groups, correlations between BV/TV and CartVol were not significant. Correlations between BV/TV and BV_sub_chonPl were significant for S2 and S3 (r=0.60 (p<0.003), r=0.45 (p<0.03), respectively) but not for S1. BV/TV and PoV/TV_sub_chonPl were significantly correlated r=-0.73 (p<10 –4 ) for S3 but not for S1 and S2. CartVol was significantly correlated with with BV_sub_chonPl r=0.72 (p<10 –4 ) and PoV/TV_sub_chonPl r=-0.51 (p<0.01) for S1 but not for S2 or S3. Conclusions: In non OA knees, the relationships between CartVol, BV_sub_chonPl and porosity with subchondral trabecular bone volume are location dependent. In an inner position (S2), which is never covered by the meniscus, CartVol, BV_sub_chonPl, and the trabecular bone parameters BV/TV and Tb.Th were higher and DA was lower compared to the lateral (S3) and posterior (S1) locations, which are usually covered by the meniscus. We conclude that the location in the tibial medial plateau and the presence of the meniscus play an important role on the surrounding structures such as cartilage, subchondral plate and trabecular subchondral bone. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4404